1993
DOI: 10.1034/j.1399-3054.1993.880224.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-butyric acid in plants: occurrence, synthesis, metabolism and transport

Abstract: Miiller, J. 1993. Indole-3-butyric acid in plants: occurrence, synthesis, metabolism and transport. -Physiol. Plant. 88: 382-389.Indole-3-butyric acid (IBA) was recently identified by GC/MS analysis as an endogenous constituent of various plants. Plant tissues contained 9 ng g~ fresh weight of free IBA and 37 ngg 'fresh weight of total IBA, compared to 26 ngg ' and 52 ngg ' fresh weight of free and total indole-3-acetic acid (lAA), respectively. IBA level was found to increase during plant development, but nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…We incubated 8-dold seedlings in a solution containing 10 mM [ 13 C 8 -15 N 1 ] IBA and assayed levels of [ 13 C 8 -15 N 1 ]IAA after 1 h by using gas chromatography-mass spectrometry (GC-MS) with selective ion monitoring (SIM). We found that wild-type seedlings converted some of the provided IBA to IAA during the 1-h labeling period, demonstrating that Arabidopsis, like other plants (Epstein and Lavee, 1984;Epstein et al, 1989;Epstein and Ludwig-Mü ller, 1993;Ludwig-Mü ller, 2000), can use IBA as an IAA precursor. Moreover, the tir1-1 and axr2-1 auxin-signaling mutants accumulated similar levels of [ 13 C 8 -15 N 1 ]IAA as wild type (Fig.…”
Section: Iba-resistant Mutants Are Defective In Iba-to-iaa Conversionmentioning
confidence: 86%
See 2 more Smart Citations
“…We incubated 8-dold seedlings in a solution containing 10 mM [ 13 C 8 -15 N 1 ] IBA and assayed levels of [ 13 C 8 -15 N 1 ]IAA after 1 h by using gas chromatography-mass spectrometry (GC-MS) with selective ion monitoring (SIM). We found that wild-type seedlings converted some of the provided IBA to IAA during the 1-h labeling period, demonstrating that Arabidopsis, like other plants (Epstein and Lavee, 1984;Epstein et al, 1989;Epstein and Ludwig-Mü ller, 1993;Ludwig-Mü ller, 2000), can use IBA as an IAA precursor. Moreover, the tir1-1 and axr2-1 auxin-signaling mutants accumulated similar levels of [ 13 C 8 -15 N 1 ]IAA as wild type (Fig.…”
Section: Iba-resistant Mutants Are Defective In Iba-to-iaa Conversionmentioning
confidence: 86%
“…Conversion of IBA to IAA has been demonstrated in a variety of plants (Fawcett et al, 1960; for review, see Epstein and Ludwig-Mü ller, 1993) and may involve b-oxidation of the four-carbon carboxyl side chain of IBA to the two-carbon side chain of IAA (Fawcett et al, 1960;Zolman et al, 2000Zolman et al, , 2007.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that IBA is more effective than NAA in root induction of a wide variety of species, and it is used in the nursery industry for rooting several plant GAGAGAGAGAGAGAGAT 52 9 108 3 823 TCTCTCTCTCTCTCTCC 52 6 72 4 826 ACACACACACACACACC 52 7 84 5 828 TGTGTGTGT GTG TGT GA 52 6 72 6 835 AGAGAGAGAGAGAGAGYC 52 7 84 7 841 GAGAGAGAGAGAGAGAYC 52 5 60 8 843 CTCTCTCTCTCTCTCTRA 52 6 72 9 848 CACACACACACACACARG 52 6 72 10 860 TGTGTGTGTGTGTGTGAA 52 5 60 Total 63 756 species worldwide (Epstein and Luduig-Muller 1993). Here, medium supplemented with IBA showed higher rate of root induction and longer roots than control or medium supplemented with different levels of NAA.…”
Section: Discussionmentioning
confidence: 99%
“…IAA was the first used to stimulate rooting of cuttings (Cooper, 1935) and soon after another auxin which also promoted rooting, IBA, was discovered and was considered even more effective (Zimmerman and Wilcoxon, 1935). Nowadays IBA is used commercially to root microcuttings and is more efficient than IAA (Epstein and Ludwig-Müller, 1993).…”
Section: The Plant Hormone Auxinmentioning
confidence: 99%